Actor roles and networks in agricultural climate services in Ethiopia: a social network analysis - Tesfaye, Abonesh; Hansen, James; Radeny, Maren A.O.; Belay, Sebsib; Solomon, Dawit (Informa UK Limited, 2020)
This paper aims to better understand actors involved in the generation, translation, communication and governance of agricultural climate services and their networks in Ethiopia. To achieve these objectives, about 65 actor organizations were selected across seven regions and two city administrations in Ethiopia through a scoping study, extensive literature review, and snowball sampling. Structured questionnaires with closed and open-ended questions were designed to gather relevant information. Results were used to compute network size, density and centrality measures. Our findings show that climate services are regularly communicated to only 10% of the total districts (woredas) on average, with only a third of the actors involved in communicating these services. No single organization or institution plays a dominant role in production, translation, communication or governance of climate services, but a network of organizations and institutions are involved. Major challenges faced by the actors involved in production, translation and delivery of climate services included lack of human and financial resources and weak monitoring and evaluation systems. The paper highlights the importance of strengthening partnerships and networking among actors including monitoring and evaluation systems at all levels to facilitate effective production, translation and dissemination of climate services to farmers.